2018
DOI: 10.1182/blood-2017-11-815746
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin infusion for treatment of steroid-resistant acute graft-versus-host disease

Abstract: Corticosteroid resistance after acute graft-versus-host disease (SR-aGVHD) results in high morbidity and mortality after allogeneic hematopoietic cell transplantation. Current immunosuppressive therapies for SR-aGVHD provide marginal effectiveness because of poor response or excessive toxicity, primarily from infection. α-Antitrypsin (AAT), a naturally abundant serine protease inhibitor, is capable of suppressing experimental GVHD by downmodulating inflammation and increasing ratios of regulatory (T) to effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…Flow cytometry analysis was performed with fluorescently-labeled monoclonal antibodies to mouse CD4-APC (GK1.5, BioLegend) or CD8a-PE (53-6.7, BioLegend) or human CD3-PE (UCHT1, BioLegend), CD4-APC (SK3, BioLegend), and CD8a-PE (HIT8a, BiioLegend), as described previously ( 40 ). Dead cells were stained with Live/Dead Fixable Near-IR (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry analysis was performed with fluorescently-labeled monoclonal antibodies to mouse CD4-APC (GK1.5, BioLegend) or CD8a-PE (53-6.7, BioLegend) or human CD3-PE (UCHT1, BioLegend), CD4-APC (SK3, BioLegend), and CD8a-PE (HIT8a, BiioLegend), as described previously ( 40 ). Dead cells were stained with Live/Dead Fixable Near-IR (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…α 1 -Antitrypsin α 1 -Antitrypsin (AAT), a circulating protease inhibitor produced by the liver, is implicated in several aspects of immune regulation: It inactivates serine proteases from neutrophils and macrophages, induces IL-10, and suppresses plasma proinflammatory cytokines (Table 2) [89]. In murine models, AAT reduced the severity of aGVHD, reducing inflammatory cytokines and increasing the ratio of Tregs to effector T cells-this led to a phase 2 clinical trial in patients with SR-aGVHD (NCT01700036).…”
Section: Fecal Microbiota Transplantmentioning
confidence: 99%
“…Forty patients received 60 mg/kg AAT intravenously every 4 days for up to 4 weeks. At day 28, ORR and CR rates were 65% and 35%, respectively [89]. There is an ongoing early-access clinical study (NCT03172455), and AAT is also being investigated as prophylaxis for SR-aGVHD (NCT03459040).…”
Section: Fecal Microbiota Transplantmentioning
confidence: 99%
“…75 Recent small phase I and II studies demonstrated that complete responses were achievable when AAT was administered as salvage therapy. 75,76 A prospective dose-finding study used AAT in a cohort of patients (N=12) presenting with grades III or IV GI only, or GI with liver, acute GVHD who failed steroid treatment. An initial loading dose of AAT 90 mg/kg intravenous on day 1 was given followed by seven maintenance doses on days 3, 5, 7, 9, 11, 13, 15 of either 30-60 mg/kg/day depending on the dosing cohort.…”
Section: Tocilizumabmentioning
confidence: 99%
“…Administration of AAT appeared to be well tolerated, although infection was reported in 32.5% of patients, making AAT another potential treatment to consider for steroid-refractory disease. 76…”
Section: Tocilizumabmentioning
confidence: 99%